Differential Modulation Based Network Coded Cooperative Communications - Karabulut, Muhammet Ali; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2015)
Multiple access relay channel (MARC) where multiple users communicate with a common destination via a relay, is an innovative approach and one of the most important network coding applications in wireless cooperative communications in recent years. In this paper, noncoherent differential binary phase shift keying (DPSK) technique which eliminates the need for channel estimation cost is applied to the MARC system model that uses maximum likelihood detection approach at the common destination. Noncoherent DPSK modulation of the MARC system model provides full diversity gain that has been observed at the resulting Monte-Carlo simulation.
Keywords: Differential modulation; multiple access relay channel; network coding; WIRELESS SYSTEMS; Engineering; Telecommunications